Synthesis and characterization of novel polybenzimidazoles bearing pendant phenoxyamine groups - Kulkarni, Mahesh; Potrekar, Ravindra; Kulkarni, R. A.; Vernekar, S. P. (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
A novel aromatic diacid, 3, 5-dicarboxyl-4'-amino diphenyl ether, containing pendant phenoxy amine group was synthesized. Homo- and co-polybenzimidazoles containing different content of pendant phenoxyamine groups were synthesized by condensation of 3,3'-diaminobenzidine with this acid and a mixture of this acid and isophthalic acid in different ratio in polyphosphoric acid. Copolybenzimidazoles with structural variations were also synthesized based on this acid and pyridine dicarboxylic acid, terephthalic acid, adipic acid, or sebacic acid. The polymers have good solubility in polar aprotic solvents and strong acids and they form tough flexible films by solution casting. The polymers were characterized by different instrumental techniques (FTIR, TGA, DSC, XRD, etc.) and for solvent solubility, mechanical properties, inherent viscosity, and proton conductivity. The inherent viscosities of the polymers vary in the range of 0.62-1.52 dL/g. They have high thermal stability up to 475506 degrees C (IDT) in nitrogen, high glass transition temperatures (T-g) ranging from 313 to 435 degrees C and good tensile strength ranging from 58 to 125 MPa. Proton conductivity of homo polymer is 3.72 x 10(-3) S/cm at 25 degrees C and 2.45 x 10(-2) S/cm at 200 degrees C (c) 2008 Wiley Periodicals, Inc.
Keywords: Characterization; copolybenzimidazoles; High performance polymers; high temperature materials; pendant phenoxyamine group; polybenzimidazoles; synthesis